When the aortoiliac bifucation is occluded:Leriche syndrome. (March 2022) - Adnor, Said; El Kourchi, Mehdi; Wakrim, Soukaina
Abstract: Intoduction: Leriche syndrome is a special type of obliterating arterial disease of the lower limbs which results in thrombotic occlusion of the aortoiliac junction. Case report: We report the case of a 65-year-old patient with known cardiovascular and nephrological pathological history, who presented with acute abdominal pain with intermittent claudication of the lower limbs and in whom clinical examination found abolition of the femoral pulses. Discussion: Doppler ultrasound of the abdominal aorta revealed aortic thrombosis in the lower of the renal segment extended to the iliac bifurcation with damping of upstream circulatory speeds. We supplemented with a CT angiography of the aorta and lower limbs which demonstrated extensive arterial thrombosis from the abdominal aorta to the bilateral external iliac arteries. Highlights: Leriche syndrome is a special type of obliterating arterial disease of the lower limbs. It's Responsible of a unique triad of symptoms, including claudication, impotence, and decreased peripheral pulses. The diagnosis is suspected clinically, objectified by Doppler ultrasound and detailed by CT angiography. CT angiography is the examination of choice in the diagnosis of Leriche syndrome.